2017
DOI: 10.1128/jcm.02319-16
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Electronic Tracking of Diarrheal Episodes and Laxative Therapy Enables Verification of Clostridium difficile Clinical Testing Criteria and Reduction of Clostridium difficile Infection Rates

Abstract: Health care-onset health care facility-associated Clostridium difficile infection (HO-CDI) is overdiagnosed for several reasons, including the high prevalence of C. difficile colonization and the inability of hospitals to limit testing to patients with clinically significant diarrhea. We conducted a quasiexperimental study from 22 June 2015 to 30 June 2016 on consecutive inpatients with C. difficile test orders at an academic hospital. Real-time electronic patient data tracking was used by the laboratory to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 31 publications
(40 reference statements)
0
46
0
Order By: Relevance
“…Overall, with the approach undertaken in this study, PCR could sensitively detect presence of toxigenic C. difficile (4), sensitively predict fecal free toxin, and predict toxin-negativity with a high NPV. Compared to current practices at our institution and other U.S. hospitals where nearly all patients with positive C. difficile PCR results are treated for CDI (16,17), reporting C T toxin result in addition to PCR result has the potential to reduce anti-C. difficile therapy by 45.8% based on results of this study (143 of 312 PCR-positive samples were C T toxin negative), if only toxin-positive patients are treated. This approach has the potential to have far-reaching impact as stand-alone C. difficile NAAT has been widely adopted for CDI diagnosis in the United States (18).…”
Section: Discussionmentioning
confidence: 98%
“…Overall, with the approach undertaken in this study, PCR could sensitively detect presence of toxigenic C. difficile (4), sensitively predict fecal free toxin, and predict toxin-negativity with a high NPV. Compared to current practices at our institution and other U.S. hospitals where nearly all patients with positive C. difficile PCR results are treated for CDI (16,17), reporting C T toxin result in addition to PCR result has the potential to reduce anti-C. difficile therapy by 45.8% based on results of this study (143 of 312 PCR-positive samples were C T toxin negative), if only toxin-positive patients are treated. This approach has the potential to have far-reaching impact as stand-alone C. difficile NAAT has been widely adopted for CDI diagnosis in the United States (18).…”
Section: Discussionmentioning
confidence: 98%
“…4 Appropriate testing for CDI is critical given the inability of current testing to distinguish between asymptomatic carrier and disease state. Truong et al 9 recently reported a significant decrease in C. difficile test utilization from 208.8 to 143 tests per 10,000 patient days and a decrease in healthcare facility-onset CDI of >25% (ie, from 13.0 to 9.7 cases per 10,000 patient days) using real-time electronic data to enforce laboratory testing criteria, which they defined as the presence of diarrhea and absence of laxative use in the prior 48 hours. 9 In addition to improving testing cascades for CDI by limiting specimens from patients receiving laxatives, education must also engage the nursing staff.…”
mentioning
confidence: 99%
“…3,7,8 Interventions to reduce the testing of inappropriate specimens, including those due to laxative use, have led to a reduction of CDI rates and treatment. 9 We further examined the relationship between laxative use and patients who tested positive for CDI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Journal of Clinical Microbiology, Truong et al (J. Clin. Microbiol., 55:1276 -1284, 2017, https://doi.org/10.1128/JCM.02319-16) report significant reductions in hospital-onset CDI and oral vancomycin utilization at their institution following implementation of a novel intervention that leveraged their clinical bioinformatics resources to prevent C. difficile testing of stools from patients without clinically significant diarrhea and in patients with recent laxative use. …”
mentioning
confidence: 99%